An Upgraded Lithium Ion Battery Based on a Polymeric Separator Incorporated with Anode Active Materials. Issue 15 (18th February 2019) - Chen, Dongjiang; Zhou, Ziqi; Feng, Chao; Lv, Weiqiang; Wei, Zhaohuan; Zhang, Kelvin H. L.; Lin, Bin; Wu, Songhao; Lei, Tianyu; Guo, Xuyun; Zhu, Gaolong; Jian, Xian; et al.
Abstract: Structural/compositional characteristics at the anode/electrolyte interface are of paramount importance for the practical performance of lithium ion batteries, including cyclic stability, rate capacity, and operational safety. The anode‐electrolyte interface with traditional separator technology is featured with inevitable phase discontinuity and fails to support the stable operation of lithium ion batteries based on large‐capacity anodes with structural change in charges/discharges, such as transition metal oxide anodes. In this work, an anode/electrolyte framework based on an oxide anode and an active‐oxide‐incorporated separator is proposed for the first time and investigated for lithium ion batteries. The architecture builds a robust anode‐separator interface in LIBs, shortens Li + diffusion path, accelerates electron transport, and mitigates the volume change of the oxide anode in electrochemical reactions. Remarkably, 4 wt% CuO addition in the separator leads to a 17% enhancement in the overall capacity of a battery with a CuO anode. The battery delivers an unparalleled record reversible capacity of 637.2 mAh g −1 with a 99% capacity retention after 100 charge/discharge cycles at 0.5 C. The high performance are attributed to the robust anode‐separator interface, which gives rise to enhanced interaction between the oxide anode and the same‐oxide‐incorporated composite in the separator. Abstract : A novel anode/separator architecture based on oxide anode and active‐oxide‐incorporated separators is proposed for the first time. The phase‐matched architecture with a strong interaction between CuO and the CuO‐incorporated separator gives rise to a record 99% capacity retention due to the shortened Li + diffusion path, accelerated electron transport, and mitigated volume change of the oxide anode.